Sirr Ikhtilaf al-Ifrad wa al-Jama’ Lafdz al-Sama’ wa al-Abshar wa al-Af’idah Fi al-Qur’an al-Karim - Muhammad Hanif Fauzi; Muhammad Zuhdi Fauzi; Agus Yasin (Universitas Darussalam Gontor, 2022)
The discussion of the word forms ifrad (singular) and jama '(plural) in the Qur’an has a uniqueness that needs to be explored. We can take lessons from the meanings contained in its use. The word sama ', abshar and afi'dah in the Qur'an. The discussion that is being studied is al-I'jaz al-I'lmi in the verses of the al-Qur'an which contain the same words', abshar and afi'dah. The author uses a descriptive-analysis method in collecting research data. The conclusion of this research is the word form ifrad from sama' is a privilege given by Allah SWT in human creation where the sense of hearing is the same as an unlimited sense means that it includes all forms of sound from various directions, different from the sense of sight whose ability is limited by the field of view. The fresh senses are also the first human senses to do their duty compared to other human senses.